Drivers, practices and performances of green supply chain management of ISO 14001 certified manufacturers in Malaysia - Rusli, Khairul Anuar (2012)
The emergence of attention towards the prospects of South East Asia becoming a new centre for manufacturing industry is expected to create more job and business opportunities in the future. Despite the rapid changes in world development, the effect and consequences of manufacturing activities in the supply chain process has been widely discussed. An increasing amount of research into the underlying dimensions of greening the supply chain (GSCM) is gaining momentum and offers a lot of discoveries to be explored especially in the context of developing countries since more focus have been given to the developed countries in previous research. Thus, this study bridge the gap by examines the GSCM drivers, practices and performances of ISO 14001 certified manufacturers in Malaysia. This study posits several hypotheses to examine the relationship between green supply chain drivers, practices and performances. This study also hypothesises that trust ~and commitment moderates the relationship between green practices and GSCM performances. Data was collected through interview sessions with representative from four selected manufacturers and self-administered questionnaires that were sent to respondents in the target sample which was drawn from a list of IS014001 manufacturers obtained from the Federation of Malaysia Manufacturers (FMM) 2010. A total of 112 usable responses were received and used for the data analysis. Pearson's correlation and multiple regression analysis were used for the hypotheses testing in this study. The qualitative data from the interviews were used to further support the findings. It can be conclude that manufacturers in Malaysia received high pressures to adopt GSCM however, the implementation and the outcomes for the GSCM practices still at par. The results provided support for four hypotheses posited in the research framework. Significantly, the findings indicated that Green Supply Chain Management (GSCM) drivers were positively related to GSCM practices. Meanwhile the elements of trust and commitment moderate the relationships between GSCM practices and environmental performances. However, the findings failed to find significant evidence on the moderating effect of trust and commitment on GSCM practices, and the other two outcomes indicators which were market/financial performances and customer satisfaction. The overall findings thus seem to support the theoretical model of the research.